Efektivitas Penerapan Sistem Absensi Wajah (Face Recognition) ‘Sibegawan’ dalam Meningkatkan Disiplin Kerja Pegawai pada PT BPR Bank Jombang Perseroda - Al Rofiqi, Izzatul Lutfiyah; Rizqi, Maulidyah Amalina (IAI Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to determine the effectiveness of the implementation of the facial recognition attendance system 'Sibegawan' in improving the work discipline of employees at PT. BPR Bank Jombang Perseroda. This is based on effectiveness indicators, namely target achievement, adaptability, job satisfaction, and responsibility. This type of research is descriptive qualitative research, with data collection using interviews with 3 informants to obtain data, followed by data analysis using the Miles & Huberman model. The results of this study indicate that the effectiveness of the implementation of the 'Sibegawan' facial recognition attendance system in improving the work discipline of employees at PT. BPR Bank Jombang Perseroda is good. With the implementation of the facial recognition attendance system 'Sibegawan' and the enforcement of employee discipline rules, employees comply with the existing regulations, such as penalties for tardiness, including the deduction of attendance allowances, which enables employees to perform their duties well and increases their discipline level.